Preferred by “All” and Preferred by “Most” Decision Makers: Almost Stochastic Dominance - Leshno, Moshe; Levy, Haim (Management Science, 2002)
While “most” decision makers may prefer one uncertain prospect over another, stochastic dominance rules as well as other investment criteria, will not reveal this preference due to some extreme utility functions in the case of even a very small violation of these rules. Such strict rules relate to “all” utility functions in a given class including extreme ones which presumably rarely represents investors' preference. In this paper we establish almost stochastic dominance (ASD) rules which formally reveal a preference for “most” decision makers, but not for “all” of them. The ASD rules reveal that choices which probably conform with “most” decision makers also solve some debates, e.g., showing, as practitioners claim, an ASD preference for a higher proportion of stocks in the portfolio as the investment horizon increases, a conclusion which is not implied by the well-known stochastic dominance rules.